Quick & easy low-sugar recipes : lose weight, boost energy, fight fatigue - Graimes, Nicola (Wells Street, London : Watkins Publishing, 2010)
Eating low-sugar foods doesn't have to mean being condemned to a dull diet. This book features one hundred easy-to-follow recipes that are divided into Breakfasts & Brunches, Lunches & Dinners. It also includes delicious family favourites such as fruit crumbles, sponge puddings, biscuits and cakes
1. Basic low-sugar recipes -- 2. Breakfasts & brunches -- 3. Light meals & snacks -- 4. Dinners -- 5. Desserts -- 6. Cakes, bakes -- 7. Cakes, bakes & breads
"Simply healthy"--Cover
Includes index
Keywords: Low-calorie diet -- Recipes; Sugar-free diet -- Recipes